2020
DOI: 10.1175/jas-d-19-0172.1
|View full text |Cite
|
Sign up to set email alerts
|

Convective Coupling in Tropical-Depression-Type Waves. Part I: Rainfall Characteristics and Moisture Structure

Abstract: Tropical-depression (TD)-type waves are synoptic-scale disturbances embedded with deep convection over the western North Pacific. Studies of these disturbances began over six decades ago; however, some properties of these disturbances remain vague, e.g., the coupling mechanism between the deep convection and the waves. This two-part study aims to examine the rainfall progression in TD-type disturbances and associated tropospheric moisture controlling convective rainfall. Part I investigates the rainfall and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…On the contrary, TD frequency modulation is stronger over Africa and the Atlantic, as well as the Pacific. These regions are known for strong easterly wave activity during northern summer and fall (Cheng et al, 2019;T. Feng et al, 2020;Kiladis et al, 2006;Rydbeck & Maloney, 2014).…”
Section: Climatological and Ccew-modulated Mcs Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, TD frequency modulation is stronger over Africa and the Atlantic, as well as the Pacific. These regions are known for strong easterly wave activity during northern summer and fall (Cheng et al, 2019;T. Feng et al, 2020;Kiladis et al, 2006;Rydbeck & Maloney, 2014).…”
Section: Climatological and Ccew-modulated Mcs Frequencymentioning
confidence: 99%
“…On the contrary, TD frequency modulation is stronger over Africa and the Atlantic, as well as the Pacific. These regions are known for strong easterly wave activity during northern summer and fall (Cheng et al., 2019; T. Feng et al., 2020; Kiladis et al., 2006; Rydbeck & Maloney, 2014). Lastly, the modulation by the MJO appears stronger over the Eastern than Western Hemisphere, consistent with the MJO's strong precipitation and circulation patterns over the warm pool (M. C. Wheeler & Hendon, 2004; Zhang, 2005).…”
Section: Climatological and Ccew‐modulated Mcs Frequencymentioning
confidence: 99%
“…The NH precipitation structure shares some similarities with other studies of TEWs in the North Pacific Ocean. Feng et al (2020) found that the greatest rain rates associated with TEWs in the western North Pacific Ocean were located equatorward of the cyclonic vorticity maximum. Huaman et al (2021) also showed the deepest convection south of the TEW trough center for TEWs in the eastern North Pacific.…”
Section: Discussionmentioning
confidence: 97%
“…Different types of SSWs may induce distinct moisture structures and modulate the characteristics of tropical rainfall. For example, the spatial structure of TD-type SSWs, in which the coupled in-phase vortex and deep convection slightly precede shallow convective rainfall, is different from the common progressive "shallow-to-deep-to-stratiform rainfall" paradigm (Kiladis 2009;Feng et al 2020a). Moreover, SSWs directly provide a common precursor disturbance for TC genesis and indirectly provide a favorable environment for TC genesis by enhancing local convection and the associated lower-level cyclonic winds (Frank and Roundy 2006).…”
Section: Introductionmentioning
confidence: 98%